Monitoring localized changes of Cr(VI) bioavailability related to root-induced changes around rice roots - Liu, Zhaodong; Wang, Haicui; Zhang, Hanlin; Jing, Yongping; Bo, Luji; Zhong, Ziwen; Wang, Guifeng; Wang, Yanqin; Li, Yan (Rhizosphere, 2023)
Transformation between Cr(III) and Cr(VI) occurs in Cr-contaminated soils. Although redox conditions and biotic/microbial activity are known to be important factors in determining Cr transformation and accumulation in soil-rice systems, how spatial trends and speciﬁc soil processes regulate Cr behaviour around lowland/ﬂooded rice roots are poorly understood. In this study, the Cr(VI) bioavailability was evaluated using the diffusive gradients in thin film (DGT) technology. Root activity reduced Cr(VI) bioavailability. The Cr(VI) flux near rice roots was 1.27–3.92 times lower than that in bulk soil (0.94 ng cm⁻² h⁻¹). The radial extension of the strong influence zone (R1) in the rhizosphere of C-LYZ was smaller than that in Hui-LY985. Although Fe(II) and S²⁻ were involved in Cr(VI) reduction, they were not the primary influence, especially for the rhizosphere region. The high phosphate concentration in the C-LYZ rhizosphere hindered Cr(VI) uptake. The DGT technique overcomes the limitations of traditional research methods, revealing the spatial variability in Cr(VI) and its interactions with other elements in the rhizosphere, thereby providing theoretical basis for bioavailability evaluation and remediation of Cr-contaminated soils.